Innovative dimension of using telematics tools in training processes of young football players - Kęsicki, Grzegorz; Lewicki, Wojciech (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The article presents the considerations concerning the use of telematics solutions, as tools for measuring efficiency and physical fitness of modern football players. Aim of Study. The aim of the study is to show that the distance covered at various intensity thresholds is the factor defining the effort performed by the football player in match conditions. This parameter is a much more reliable measure than the total distance travelled or the maximum speed achieved by the player. Material and Methods. Data that are the subject of the research were collected using the CATAPULT system equipped with the GPS transmitters. For empirical purposes, the author’s studies have been presented concerning the indicators that characterise the performance of football players’ work when performing acceleration and the distances covered during slowdown at different levels of intensity The use of a suitable statistical tool in the form of Excel computer program allowed, among others, to determine the mean distance travelled by players during accelerations and slowdowns at different intensity thresholds and average total distance and average maximum speeds. Results. Among the players covered with the study it was found that the average distance travelled during the accelerations and slowdowns at different intensity thresholds drops during the next five-minute intervals in each half of the match played. However, a similar relationship does not exist for the average total distance and averaged maximum speeds. Moreover, it has been shown that after a 15-minute break the average value of the distance travelled increases significantly during accelerations and slowdowns in relation to the last measured time interval for the first half. Conclusions. Implementation of science to the world of sports made it possible to say that the distance covered at different intensity thresholds is a more reliable measure that defines the effort made by the football player in match conditions than the total distance travelled or the maximum speed achieved by the football player.
Keywords: telematics; innovation; youth sport; football; training processes; physical parameters measurement